Transforming Lecturers for Evolving Education: Addressing the Knowledge and Skills Gap in Education 5.0 Era - Dadirayi, Mudzengerere (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
Education 5.0 reaffirms the primacy of universities, polytechnics, teachers’ colleges and industrial training colleges in economic growth, technological transfer and generation of new knowledge. The paper examines the knowledge and skills gap among lecturers in the context of Education 5.0, an era defined by its emphasis on the integration of teaching, research, community service, innovation and industrialisation. The study argues that without targeted professional development and support, lecturers may struggle to meet the expectations of a modernised curriculum. Through a synthesis of literature and practical insights, the study proposes a framework for transforming lecturer competencies that aligns with the goals of Education 5.0. The framework explores strategic interventions, including continuous professional development programs, pedagogical innovation, and technological integration, which enhance lecturer proficiency. Best practices from higher teacher education institutions illustrate effective transformation strategies, ensuring quality teacher preparedness for 21st-century learning. Through an examination of the current educational reforms and the associated challenges faced by lecturers, this chapter sets the stage for a deeper understanding of the transformation required within teacher education in Zimbabwe. In conclusion, the Education 5.0 era presents transformative opportunities for the higher education sector, driven by the five tenets of teaching, research, community engagement, innovation and industrialisation.